Information support for monitoring of the organization state - Lyudmila V. Borisova; Lyubov A. Dimitrova; Inna N. Nurutdinova (Advanced Engineering Research)
The paper objective is the preparation, processing and analysis of the expert information to determine the organization maturity level on the basis of the self-assessment. GOST R ISO 9004-2010 criteria are used to establish the maturity level. The following tasks are set: to determine the sequence of actions for assessing the maturity level of the organization, and to develop methods of generating the expert information that gives an adequate view of the actual situation. A mathematical apparatus of fuzzy sets theory is used to solve the problems. The preparation and analysis of the expert information is the gist of the fuzzification stage in creating an expert system. The solution to the problem is illustrated by a model example. Linguistic variables and additive and multiplicative indices of conformity are determined. Membership functions and matrices of consistency and of fuzziness indexes are constructed. The program system of expert information input is used to obtain these characteristics. Sufficiently high quality of the expert information and its applicability on the subsequent stages of the expert system operation are determined. The proposed methods can be applied both for the expert information generation under determining the organization maturity level, and for solving any problem of the development of the expert systems that operate on the basis of the fuzzy expert information.